2010
DOI: 10.1177/1367006910379262
|View full text |Cite
|
Sign up to set email alerts
|

Physiological reactivity to emotional phrases in Mandarin—English bilinguals

Abstract: Chinese—English bilinguals residing in the US were interviewed about their experience of using emotional expressions. They judged L1-Mandarin expressions as feeling stronger than L2-English expressions. Respondents nonetheless preferred to express their emotions in English, citing more relaxed social constraints in English-speaking environments. Electrodermal monitoring was conducted on a similar sample of Chinese—English bilinguals in order to determine how physiological reactivity corresponds to self-reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 44 publications
(62 reference statements)
8
82
3
Order By: Relevance
“…Overall, our results fall in line with previous findings based on skin-conductance (e.g., (2022)) as well as pupillometry (32), suggesting that emotion word processing, and specifically emotional resonance in L1 vs. L2, is linked to activation in the Autonomic Nervous System. Thus, our study contributes to a growing body of work suggesting that (bilingual) word processing is partially grounded in physiological reactions to emotion, and that reduced emotional resonance can be detected with physiological measures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our results fall in line with previous findings based on skin-conductance (e.g., (2022)) as well as pupillometry (32), suggesting that emotion word processing, and specifically emotional resonance in L1 vs. L2, is linked to activation in the Autonomic Nervous System. Thus, our study contributes to a growing body of work suggesting that (bilingual) word processing is partially grounded in physiological reactions to emotion, and that reduced emotional resonance can be detected with physiological measures.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Mandarin-English bilinguals showed no significant differences in emotional SCRs between languages, except for L2 endearments, which again elicited a higher emotional response than their L1 counterparts. The authors conjectured that these unexpected aspects of the findings could be explained by cross-cultural differences in norms of emotional expression (22).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the large number of diverse participants confers considerable statistical power, useful for discerning broad patterns of response. These patterns were then examined in studies with smaller populations, which combined the original or modified versions of the BEQ with interviews (e.g., Caldwell‐Harris, Tong, Lung, & Poo, 2011; Dewaele, 2010).…”
Section: Affective Processing In Bilingual Speakersmentioning
confidence: 99%
“…Caldwell‐Harris et al. (2011) found that late Mandarin–English bilinguals judged the L1 Mandarin to be more emotional, while early bilinguals judged the two languages as equally emotional. Caldwell‐Harris, Staroselsky, Smashnaya, and Vasilyeva (2012) found order of acquisition and AoAr effects: perceived emotionality of L1 Russian was highest in Russian–English bilinguals who arrived in the US after the age of 10 (late arrivals), lower (but not significantly) in bilinguals who arrived prior to age 10 (early arrivals), and significantly lower in English–Russian bilinguals who learned Russian as FL or L2 (Table 2).…”
Section: Affective Processing In Bilingual Speakersmentioning
confidence: 99%
See 1 more Smart Citation